2020
DOI: 10.1177/0003134820981683
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perianal Tramadol Infiltration on Postoperative Pain Following Hemorrhoidectomy

Abstract: Introduction The present study was attempted to evaluate the effect of perianal infiltration of tramadol on postoperative pain in patients undergoing hemorrhoidectomy. Method This double-blind clinical trial study was carried out on 90 patients with grade 3 and 4 hemorrhoids undergoing hemorrhoidectomy. Patients were randomly assigned into 3 groups of control or bupivacaine or tramadol. Before the surgery, perianal infiltration of .25% bupivacaine or tramadol or normal saline was prescribed to each group, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Furthermore, 65 irrelevant studies and 1 non-English study were excluded based on full-text reading. Finally, 18 eligible studies were included in our meta-analysis ( Jirasiritham et al, 2004 ; Naja et al, 2005 ; Ng et al, 2006 ; Imbelloni et al, 2007 ; Gorfine et al, 2011 ; Haas et al, 2012 ; Rajabi et al, 2012 ; Moreira et al, 2014 ; Sim and Tan, 2014 ; Farag and Esmat, 2016 ; Shashikala and Prathibha, 2016 ; Ruiz-Castro et al, 2017 ; Chitty et al, 2022 ; Cui et al, 2022 ; Hatami et al, 2022 ; Medina-Gallardo et al, 2022 ; Steen et al, 2022 ; Shahrokhzadeh et al, 2023 ). The characteristics of the 18 eligible studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, 65 irrelevant studies and 1 non-English study were excluded based on full-text reading. Finally, 18 eligible studies were included in our meta-analysis ( Jirasiritham et al, 2004 ; Naja et al, 2005 ; Ng et al, 2006 ; Imbelloni et al, 2007 ; Gorfine et al, 2011 ; Haas et al, 2012 ; Rajabi et al, 2012 ; Moreira et al, 2014 ; Sim and Tan, 2014 ; Farag and Esmat, 2016 ; Shashikala and Prathibha, 2016 ; Ruiz-Castro et al, 2017 ; Chitty et al, 2022 ; Cui et al, 2022 ; Hatami et al, 2022 ; Medina-Gallardo et al, 2022 ; Steen et al, 2022 ; Shahrokhzadeh et al, 2023 ). The characteristics of the 18 eligible studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Bupivacaine is a long-term local anesthetic drug that provides non-opioid analgesic effects by inhibiting the initiation and transmission of nerve impulses ( Farag and Esmat, 2016 ; Chitty et al, 2022 ). Previous studies have reported the analgesic effect and safety of bupivacaine in patients undergoing hemorrhoidectomy ( Hatami et al, 2022 ; Steen et al, 2022 ), while some limitations existed in the individual original studies, such as smaller sample size or performed in only one region. The meta-analysis could combine the results of two or more individual studies and demonstrate a good evidence advantage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reviewing the literature, the physio pathological background for the pain seems to be the reflex contraction of the internal anal sphincter, regarding the surgical trauma, a contraction that outlasts the pain-free interval that spinal anesthesia offers. Therefore, the use of long-lasting local anesthetics (LA), such as Bupivacaine or Tetracaine, is highly recommended by some authors[ 8 - 13 ]. However, our experience differs, as in our study, where surgeries were performed under spinal anesthesia (SA) with Marcaine (0.5% Bupivacaine), since the standard OH can be done in a 30-40 min timeframe, administering a long-lasting LA at the end of the procedure would overlap the pain free interval by almost 90% of the SA, leaving just about 30 minutes, on average, of supplementary protection against pain.…”
Section: Resultsmentioning
confidence: 99%